2018
DOI: 10.1136/bmjoq-2018-000385
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication of patient issues on transfer out of intensive care

Abstract: The written medical handover document is frequently poor in quality and highly variable which raises concerns about patient safety. Intensive care unit (ICU) patients have complex medical and social issues which increases the risk of errors during ongoing hospital treatment. Our project team of four doctors and two nurses aimed to improve the documentation of patient problems as they leave the ICU.A literature review and process mapping of both medical and nursing transfer documentation helped in understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Um mapeamento realizado com documentos de transferência corrobora estes achados ao evidenciar variabilidade e inconsistência, tais documentos sendo sinalizados pela equipe receptora como incompletos e de baixa qualidade. Como causa apontada para a problemática cita-se as trocas de profissionais nos turnos de trabalho como fator influente para desconhecimento de todas as informações do paciente (16) .…”
Section: Discussionunclassified
“…Um mapeamento realizado com documentos de transferência corrobora estes achados ao evidenciar variabilidade e inconsistência, tais documentos sendo sinalizados pela equipe receptora como incompletos e de baixa qualidade. Como causa apontada para a problemática cita-se as trocas de profissionais nos turnos de trabalho como fator influente para desconhecimento de todas as informações do paciente (16) .…”
Section: Discussionunclassified
“…The findings in the study showed that the communication and cooperation between ICU, ward and family members were short of effectiveness, which not only hindered the implementation of nursing safety in the transition period but also affected the transmission and acquisition of information for health promotion. Roberts et al (2018) have demonstrated that inaccuracies and omissions in information not only elevate the risk of adverse events but also reduce patient satisfaction. It is strongly recommended to combine oral and written communication to support information exchange during transitional care (Stelfox et al, 2017).…”
Section: Theme 3: the Obstacles To Maintaining Care Efficiencymentioning
confidence: 99%
“…ICU transitional care refers that ICU nurses and/or other medical workers provide ICU patients with minimal interruption and the best continuity of intensive care services to avoid the sudden interruption of intensive care after ICU transfer, which could ensure the safety of patients and improve the quality of care (Chaboyer et al, 2005). The transition period of ICU to a general ward is a complex process, which is closely related to medical errors, unplanned return to ICU, increased risk of adverse events, and even death, leading to the fragility of patients and the need for more complex care (Niven et al, 2014; Roberts et al, 2018). Coughlin et al (2018) have conducted a retrospective analysis of 446 cases who returned to the neurosurgery ICU within 3 years, displaying that the readmission rate was 39% in ICU, of which 17% of patients died in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Estratégias de melhorias, como treinamentos às habilidades de comunicação verbal também devem ser realizadas, assim como o acompanhamento das medidas estabelecidas. Questionários de satisfação são úteis a este respeito (Arora e Johnson, 2006) e a adoção de políticas e intervenções ao aprimoramento das rotinas deve incluir estratégias de reavaliações e reciclagens, como PDSA (Plan, Do, Study, Act) Planejar, Realizar, Estudar e Atuar (Roberts et al, 2018). A escolha do melhor local para transferência de informações é importante.…”
Section: Padronizações E Métodos Mnemônicos Utilizados No Processo De Transferência De Informaçõesunclassified